The Influence of Perceived Return Level and Financial Literacy Level on Individual Stock Investment Decision Making: Pengaruh Tingkat Persepsi Return dan Tingkat Literasi Keuangan Terhadap Pengambilan Keputusan Berinvestasi Saham Secara Individu - Aicha Ari Romadona; Wisnu Panggah Setiyono (Academia Open, 2021)
The purposes of this study are 1) To analyze the effect of perceived return on stock investment decision making. 2) To analyze the effect of financial literacy on stock investment decisions. 3) To analyze the effect of perceived returns and financial literacy on stock investment decisions. This study uses a quantitative approach, by collecting questionnaire data and using purposive sampling technique. The sample used as many as 100 investors Capital market Community Surabaya and surrounding areas. The data analysis technique used is the inner model test, outer model test and hypothesis testing using the SmartPLS version 3.0 program. The results of this study obtained based on the validity test of the questionnaire statement were declared valid. For the reliability test of the Cronbach alpha value of > 0.7, it is declared reliable. And to test the hypothesis based on the value of the inner weight on the Path Coefficients, it shows that tcount for variables X1 and X2 has a significant positive effect. The results of tcount for Perceived Return (X1) are 2,908 and financial literacy are 2.292.